Plant Growth Promotion by Two Volatile Organic Compounds Emitted From the Fungus Cladosporium halotolerans NGPF1 - Jiang, Lingmin; Lee, Myoung Hui; Kim, Cha Young; Kim, Suk Weon; Kim, Pyoung Il; Min, Sung Ran; Lee, Jiyoung (Frontiers in Plant Science, 2021)
Microbial volatiles have beneficial roles in the agricultural ecological system, enhancing plant growth and inducing systemic resistance against plant pathogens without being hazardous to the environment. The interactions of plant and fungal volatiles have been extensively studied, but there is limited research specifically elucidating the effects of distinct volatile organic compounds (VOCs) on plant growth promotion. The current study was conducted to investigate the impact of VOCs from Cladosporium halotolerans NGPF1 on plant growth, and to elucidate the mechanisms for the plant growth-promoting (PGP) activity of these VOCs. The VOCs from C. halotolerans NGPF1 significantly promoted plant growth compared with the control, and this PGP activity of the VOCs was culture medium-dependent. Headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS) identified two VOC structures with profiles that differed depending on the culture medium. The two compounds that were only produced in potato dextrose (PD) medium were identified as 2-methyl-butanal and 3-methyl-butanal, and both modulated plant growth promotion and root system development. The PGP effects of the identified synthetic compounds were analyzed individually and in blends using N. benthamiana plants. A blend of the two VOCs enhanced growth promotion and root system development compared with the individual compounds. Furthermore, real-time PCR revealed markedly increased expression of genes involved in auxin, expansin, and gibberellin biosynthesis and metabolism in plant leaves exposed to the two volatile blends, while cytokinin and ethylene expression levels were decreased or similar in comparison with the control. These findings demonstrate that naturally occurring fungal VOCs can induce plant growth promotion and provides new insights into the mechanism of PGP activity. The application of stimulatory volatiles for growth enhancement could be used in the agricultural industry to increase crop yield.